Identification of Taenia from child of 6 year old - Sah , R; Khadka , S; Sherchand , JB; Tandukar , S; Bhandari , D; Shrestha , L; Rijal , B; Pokharel , BM (Journal of Institute of Medicine Nepal, 2015)
N/A